2017
DOI: 10.18632/oncotarget.20622
|View full text |Cite
|
Sign up to set email alerts
|

Central role of mTORC1 downstream of YAP/TAZ in hepatoblastoma development

Abstract: Hepatoblastoma (HB) is the most common type of liver malignancy in children. Recent studies suggest that activation of Yes-associated protein (YAP) is a major molecular event in HB development, as activated YAP synergizes with mutant β-catenin to promote HB formation in mice (YAP/β-catenin). However, how YAP regulates HB development remains poorly defined. Similarly, de-regulation of mammalian target of rapamycin complex 1 (mTORC1) signaling has been implicated in multiple tumor types, but its functional role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…28 More important, we have recently shown that YAP is activated in both HB cell lines. 31 In light of this body of information, dnTEAD2 was overexpressed in HepG2 and Hep293TT cells. As expected, dnTEAD2 effectively inhibited the expression of Yap downstream targets, such as cysteine-rich angiogenic inducer 61 (CRY61), connective tissue growth factor (CTGF ), AXL receptor tyrosine kinase (AXL), and baculoviral IAP repeat containing 5 (BIRC5, alias SURVIVIN) in HepG2 and Hep293TT cells (Supplemental Figure S1A).…”
Section: Results Dntead2 Inhibits Hb Growth In Vitro and In Vivomentioning
confidence: 99%
“…28 More important, we have recently shown that YAP is activated in both HB cell lines. 31 In light of this body of information, dnTEAD2 was overexpressed in HepG2 and Hep293TT cells. As expected, dnTEAD2 effectively inhibited the expression of Yap downstream targets, such as cysteine-rich angiogenic inducer 61 (CRY61), connective tissue growth factor (CTGF ), AXL receptor tyrosine kinase (AXL), and baculoviral IAP repeat containing 5 (BIRC5, alias SURVIVIN) in HepG2 and Hep293TT cells (Supplemental Figure S1A).…”
Section: Results Dntead2 Inhibits Hb Growth In Vitro and In Vivomentioning
confidence: 99%
“…However, targeting GOF CTNNB1 mutations is particularly challenging. Besides β‐catenin, previous data indicate the YAP pathway as a potentially important target for the treatment of HB 12,22,23 . Recently, it was found that YAP regulates gene transcription through its interaction with the mediator/CDK9 complex 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids used in this study, including pT3‐EF1α‐∆N90‐β‐catenin, pT3‐EF1α‐YAPS127A, pT3‐EF1α‐GFP‐shLuc (where Luc is luciferase), and pCMV sleeping beauty (SB) transposase, have been described previously 22,23 . The pT3‐EF1α‐GFP‐shCdk9 construct was a generous gift from Dr. Chun‐Hao Huang from the Memorial Sloan‐Kettering Cancer Center (New York, NY).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work further showed the utility of this model. In 2017, the CTNNB1/Yap-1 model was combined with liver-specific Raptor knock-out to show a role of mammalian target of rapamycin complex 1 (mTORC1) signaling downstream of YAP-1 in HB [51]. In a second paper from 2017, Yamamoto and colleagues used the hydrodynamic tail vein injection/Sleeping Beauty transposon model to overexpress myc, Yap-1, AKT, Notch1, and Notch2 alone and in combination to generate tumors resembling HB, HCC, and cholangiocarcinoma [52].…”
Section: Models Generated With Hydrodynamic Tail Vein Injection With mentioning
confidence: 99%